Positive Impact of Professionalism on the Perception of Global Well-Being: A Study in Healthcare Professionals Starting Their First Working Experience in Peruvian Rural Areas - López-Morales, Humberto; Rivera-Diaz, Edgar; Ore-Zuñiga, Andrew; Vera-Portilla, Angel; San-Martín, Montserrat; Delgado Bolton, Roberto C.; Vivanco, Luis (Frontiers in Public Health, 2020)
Introduction: In Peru, recently graduated physicians and nurses who are willing to start working in the public healthcare system, first have to work in their newly acquired profession in the programme denominated “Servicio Rural Urbano y Marginal de Salud” (SERUMS). The SERUMS programme is a one-year contract in rural areas of the country. The aim of this study was to confirm the following hypothesis: the development of abilities associated to professionalism has a positive effect on the perception of global wellbeing in the professionals beginning SERUMS. Material and methods: In the study two cohorts of medical and nursing professionals that started SERUMS in 2017 and 2019 were included. The perception of global wellbeing and general health condition were measured with the Scale of Life Satisfaction (SWLS) and the General Health Questionnaire (GHQ-28), respectively. Professionalism was measured using Jefferson’s scales of empathy (JSE), teamwork (JSAPNC), and lifelong learning (JeffSPLL). An analysis in phases using the R language was applied to develop a multiple regression model that would explain the lineal relationship between the global perception of wellbeing and the studied variables. Results: The study sample included 303 professionals (108 men and 195 women) with a mean age of 26 years, ranging from 22 to 39 years (SD=4). Based on their profession, 230 were medical doctors and 67 were nurses. The multiple regression model evidenced that age (p<0.001), social dysfunction (p<0.001), severe depression (p<0.001), and inter-professional collaborative work abilities (p<0.001) explain 38% of the variability in the global perception of wellbeing. Moreover, a second model explained 44% of the variability in the inter-professional collaborative work abilities based on a lineal relationship with empathy (p<0.001), lifelong learning (p<0.001), and future professional orientation (p=0.01). Both models complied with the necessary conditions for statistic inference and showed large effect sizes. Conclusions: These findings confirm that professionalism has an important role in improving the global wellbeing of the professionals initiating SERUMS. This influence is direct in the case of inter-professional collaborative work, whereas it is indirect in the case of empathy and lifelong learning.